2016
DOI: 10.1002/lary.25977
|View full text |Cite
|
Sign up to set email alerts
|

Balloon dilation causing tracheal rupture: Endoscopic management and literature review

Abstract: A 72-year-old female with a history of idiopathic subglottic tracheal stenosis suffered tracheal rupture during endoscopic balloon dilation. The defect measured 7.5 cm in length, through which the mediastinum was visualized. An 80 × 20-mm silicone-covered tracheobronchial stent was deployed over the defect. The patient was extubated subsequent to intraoperative computed tomography demonstrating minimal air escape. Postoperatively, the patient saw no further complications and was discharged 3 days later. The st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…Moreover, endoscopic treatments are not fully without risk and sever complications such as tracheal laceration may develop even during dilatation. 1,16 Tracheal laceration was not observed in any of our cases subject to dilatation and both electrocautery and Nd:YAG laser were applied successfully. Thanks to the rapid symptomatic comfort it provides, dilatation enables the multidimensional assessment of patients.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…Moreover, endoscopic treatments are not fully without risk and sever complications such as tracheal laceration may develop even during dilatation. 1,16 Tracheal laceration was not observed in any of our cases subject to dilatation and both electrocautery and Nd:YAG laser were applied successfully. Thanks to the rapid symptomatic comfort it provides, dilatation enables the multidimensional assessment of patients.…”
Section: Discussionmentioning
confidence: 62%
“…It can safely be stated that the primary issue for which a consensus has been reached is that endoscopic treatments are favored more in web-like stenosis cases. 1,2,18 T tube stent became popular when Montgomery suggested the use of a silicon tracheal T tube for certain treatment of upper respiratory tract stenosis in 1974 which is known today as Montgomery T tube. 19 In addition to enabling speech, it may also be a treatment option by itself for many cases.…”
Section: Discussionmentioning
confidence: 99%
“…It can also occur spontaneously after a violent cough . Tracheal injury after balloon dilatation is rare but has been reported in the literature …”
Section: Discussionmentioning
confidence: 99%
“…10 Tracheal injury after balloon dilatation is rare but has been reported in the literature. 11,12 Sudhoff et al conducted a study on 28 cadaveric laryngotracheal specimens to investigate the pattern of tracheal injury resulting from inflation of the endotracheal tube cuff. 13 Using in vitro models they found that the typical tracheal injury pattern was a longitudinal median tear of the posterior trachea.…”
Section: Discussionmentioning
confidence: 99%
“…Excessively small diameters will not obtain significant changes and too large diameters can easily provoke complications. Mucosal and transmural tearing, bleeding, pneumomediastinum and pneumothorax have been reported [26,27]. Special caution is needed when the stenosis is not fully circumferential and the healthy posterior wall is exposed to high pressure.…”
Section: Balloon Dilatationmentioning
confidence: 99%